Secure code execution system operation algorithm - Kozachok, A.V.; Kochetkov, E.V. (Trudy Instituta sistemnogo programmirovaniâ, 2018)
The article presented a set of algorithms that form the basis of the safe code execution system. The functional purpose of it is to investigate arbitrary executable files of the operating system in the absence of source codes in order to provide the ability to control the execution of the program code within the specified functional requirements. The set of algorithms presented in this work includes: the algorithm for the functioning of a system for the safe execution of the program code; the algorithm for constructing a program model suitable for verification, which accurately preserves the properties of the source program.